RETRACTED: Biogeochemical accumulation of trace elements in soils and plants of the Russian Far East - Molchanov Vladimir (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001